A study on the retailing system of marine fish species in Iloilo City. - Joven, Rosalie Villareal
This study presented an overview of the retailing system of marine fish species in Iloilo City. It deeply looked into various components of the retailing system the costs and returns, practices, performance, structure as well as the constraints faced by the retailers. There were thirty-six (36) retailers sampled from (5) major fish distribution centers in Iloilo City namely, Central Market, Lapaz Public Market, New Jaro Market, Supermarket, and Old Jaro Market. The survey period covered the fourth week of December 1996. The data were based on their late transaction activities., Results of the study showed that during the survey period, the retailer handled thirty-four (34) marine fish species with a total volume of 2,580 kilograms and valued at 112,939.91 pesos. The top ten marine species were as follows: threadfin beam (pisugo), goatfish (salmonte), spotted moonfish (bilong-bilong), slipmouth (sapsap), yellowfin tuna (panty), big-eyed scad (bukaw), marjarras (latab), short-bodied mackerel (gumaa), yellow stripe trevally (dalinuan), and eastern little tuna (aloy). Spotted moonfish was the highest priced fish purchased by the retailers having an average value of P72.00 per kilogram. Being the highest priced fish it commanded for the highest selling price of P76.00. Mojarras, on the other hand, has the highest net margins while short-bodied mackerel posted negative net margins. However, retailing of marine fish species, on the average, showed profitability. The fish supplies mainly came from the wholesalers who accounted for 42 of the total volume handled by the retailers. Other sources included the brokers, fishermen, and co-retailers. Survey findings also showed that the retailers were already in business for an average of fourteen (14) years. Majority of them transacted business on a daily basis. Procurement of fish supplies were usually in consignment basis while sale was most often made in cash. Major problems cited were: low movement of fish demand, poor marketing facilities, shifting of consumers from traditional markets to department stores, lack of capital and the presence of talipapa outside the markets. The study suggested that good retailing facilities should be provided in each market.